IRF3 function and immunological gaps in sepsis - Basak, Bristy; Akashi-Takamura, Sachiko (Frontiers in Immunology, 2024)
Lipopolysaccharide (LPS) induces potent cell activation via Toll-like receptor 4/ myeloid differentiation protein 2 (TLR4/MD-2), often leading to septic death and cytokine storm. TLR4 signaling is diverted to the classical acute innate immune, inflammation-driving pathway in conjunction with the classical NF-κB pivot of MyD88, leading to epigenetic linkage shifts in nuclear pro-inflammatory transcription and chromatin structure-function; in addition, TLR4 signaling to the TIR domain-containing adapter-induced IFN-β (TRIF) apparatus and to nuclear pivots that signal the association of interferons alpha and beta (IFN-α and IFN-β) with acute inflammation, often coupled with oxidants favor inhibition or resistance to tissue injury. Although the immune response to LPS, which causes sepsis, has been clarified in this manner, there are still many current gaps in sepsis immunology to reduce mortality. Recently, selective agonists and inhibitors of LPS signals have been reported, and there are scattered reports on LPS tolerance and control of sepsis development. In particular, IRF3 signaling has been reported to be involved not only in sepsis but also in increased pathogen clearance associated with changes in the gut microbiota. Here, we summarize the LPS recognition system, main findings related to the IRF3, and finally immunological gaps in sepsis.